Knowledge Relations of Midwives To The Handling of Corona Virus Infection (Covid-19) on Maternity Mothers in Hospital X - Syefira Ayudia Johar (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Globally it reported 51,857 cases of confirmation in 25 countries with 1,669 deaths (CFR 3.2%). Prevention of Covid-19 is influenced by several factors, one of which is knowledge. To date, knowledge of the COVID-19 infection in conjunction with pregnancy and the fetus is still limited and there has been no specific recommendation for the treatment of pregnant women with COVID-19. The purpose of this research is to know the knowledge of midwives to the handling of Corona virus infection (Covid 19) on maternity mothers in hospital X. Research using the research design of cross sectional. Samples amounting to 30 midwives with sample techniques using sampling quotas. Analysis techniques using the Chi Square test. Results showed that there was a relationship between the knowledge of midwives to the handling of Corona virus infection (Covid 19) on maternity mothers in hospitals X